Tourism impacts towards fishermen quality of life: a conceptual framework / Zaleha Mohamad and Khyrizan Abu Jalil - Mohamad, Zaleha; Abu Jalil, Khyrizan (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This study proposed a conceptual framework on tourism impacts towards fishermen quality of life. Fishery industry is one of the significant industries in Malaysia. It is one of the huge contributors to national income. Most of the fishermen in Malaysia remain at the bottom of the social ladder in the economy. Tourism is prominently known as a dynamic and viable industry where the industry provides and contributes enormous positive impacts such as providing employment opportunities, producing return on investment, providing foreign exchange, enhancing standard of living and improving technology for the community. Tourism is also seen as a catalyst for development especially in rural areas. Currently, Setiu is famous for some tourism products such as marine, eco and agro tourism. Limited studies have been conducted on improving quality of life (QOL) of fishermen through tourism activity in Setiu. The need for the study is to make a preliminary assumption and perception of fishermen on tourism.